TASAUF SEBUAH PENDEKATAN PENDIDIKAN AKHLAQUL KARIMAH DALAM KONTEKS PEMIKIRAN QUR’ANI - Miskahuddin Miskahuddin (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Talking about Sufism, of course, cannot be separated from the efforts of a servant of Allah in his efforts to purify his personality with good deeds to produce good morals through worship to draw him closer to Allah S.W.T. based on the teachings of the Qur'an al-Karim as a guideline of his life in this world. Al-Qur'an as a way of life for all mankind is able to teach eternal goodness and as the main model that is truly perfect for moral education in order to shape the good morals of the Muslim human person, especially for those who believe in him by always studying and practicing all the contents of his teachings alone. Sincere eyes hope for the pleasure of Allah so that with Allah's permission, humans who are haqqul sure to practice it truly will certainly be able to lead them to glory and happiness both physically and mentally in this world and the safety of happiness in the hereafter. In relation to moral education for humans in the Sufism approach, it can actually be said that their efforts are trying to purify themselves which will not break away from the guidance and guidance of the Qur'an as the main basis for improving human morality so that they become obedient and ethical servants of God. karimah. Sufism as a science can be a movement of Islamic teachings that teach knowledge about how to purify the soul and clarify morals in order to build the body and mind of humans so that they can obtain true happiness in the world and also eternal happiness in the hereafter.